2018
DOI: 10.14311/app.2018.18.0077
|View full text |Cite
|
Sign up to set email alerts
|

Preprocessing of Hopkinson Bar Experiment Data: Filter Analysis

Abstract: This work presents a data preprocessing procedure for signal acquired during high strain-rate loading using a custom Split Hopkinson Pressure Bar (SHPB). Before the evaluation of the experimental data, preprocessing of the measured signals including application of suitable digital or analog filter needs to be performed. Our department mainly focuses on measurements performed on advanced materials (e.g. materials with predefined structures or hybrid foams). For such measurements, it is essential to perform data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 8 publications
(9 reference statements)
0
4
0
Order By: Relevance
“…Different theoretical analysis and single cell approach works have been conducted on estimating Poisson's ratios in tension or compressions. [49][50][51][52] The upper bound based on the rigid-rod rotational spring model showed that the upper Poisson's ratio bound of a 90 MR is around À0.45, [52] indicting a clear auxeticity, which supports the stable auxetic behavior observed. However, this work was focused on the overall deformation of samples with different-sized structures, and Poisson's ratio is calculated based on the averaged displacement of the center point of the outer column.…”
Section: Discussionmentioning
confidence: 64%
See 3 more Smart Citations
“…Different theoretical analysis and single cell approach works have been conducted on estimating Poisson's ratios in tension or compressions. [49][50][51][52] The upper bound based on the rigid-rod rotational spring model showed that the upper Poisson's ratio bound of a 90 MR is around À0.45, [52] indicting a clear auxeticity, which supports the stable auxetic behavior observed. However, this work was focused on the overall deformation of samples with different-sized structures, and Poisson's ratio is calculated based on the averaged displacement of the center point of the outer column.…”
Section: Discussionmentioning
confidence: 64%
“…The contact, sample size/cell number effects, and Poisson's ratio stability are particularly important for compression loads, as for some applications, a relatively smaller number of the cells is required, whereas for other applications, a large lattice system might be involved. Different theoretical analysis and single cell approach works have been conducted on estimating Poisson's ratios in tension or compressions . The upper bound based on the rigid‐rod rotational spring model showed that the upper Poisson's ratio bound of a 90° MR is around −0.45, indicting a clear auxeticity, which supports the stable auxetic behavior observed.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations